Prenatal Exposure to Arsenic Impairs Behavioral Flexibility and Cortical Structure in Mice - Aung, Kyaw H.; Kyi-Tha-Thu, Chaw; Sano, Kazuhiro; Nakamura, Kazuaki; Tanoue, Akito; Nohara, Keiko; Kakeyama, Masaki; Tohyama, Chiharu; Tsukahara, Shinji; Maekawa, Fumihiko (Frontiers in Neuroscience, 2016)
Exposure to arsenic from well water in developing countries is suspected to cause developmental neurotoxicity. Although it has been demonstrated that exposure to sodium arsenite (NaAsO2) suppresses neurite outgrowth of cortical neurons in vitro, it is largely unknown how developmental exposure to NaAsO2 impairs higher brain function and affects cortical histology. Here, we investigated the effect of prenatal NaAsO2 exposure on the behavior of mice in adulthood, and evaluated histological changes in the prelimbic cortex (PrL), which is a part of the medial prefrontal cortex that is critically involved in cognition. Drinking water with or without NaAsO2 (85 ppm) was provided to pregnant C3H mice from gestational days 8 to 18, and offspring of both sexes were subjected to cognitive behavioral analyses at 60 weeks of age. The brains of female offspring were subsequently harvested and used for morphometrical analyses. We found that both male and female mice prenatally exposed to NaAsO2 displayed an impaired adaptation to repetitive reversal tasks. In morphometrical analyses of Nissl- or Golgi-stained tissue sections, we found that NaAsO2 exposure was associated with a significant increase in the number of pyramidal neurons in layers V and VI of the PrL, but not other layers of the PrL. More strikingly, prenatal NaAsO2 exposure was associated with a significant decrease in neurite length but not dendrite spine density in all layers of the PrL. Taken together, our results indicate that prenatal exposure to NaAsO2 leads to behavioral inflexibility in adulthood and cortical disarrangement in the PrL might contribute to this behavioral impairment.